"Staying Well": a psychoeducational group for people with an intellectual disability, co‐morbid mental illness and offending behaviour. (2014) - Fergus Douds; Andrew McKechanie; Yasmin Simpson; Lesley Murphy
<x xml:space="preserve"> Abstract </x> Purpose – UK best practice guidelines for the treatment for people with schizophrenia recommend the use of psychoeducational approaches. The purpose of this paper is to describe the introduction of psychoeducational groups for people with an intellectual disability and co‐morbid mental illness within forensic settings. Design/methodology/approach – "Staying Well", a psychoeducational programme for people with an intellectual disability and co‐morbid mental illness was based in part on a group programme from Ashworth Hospital, but adapted and developed to be suitable for people with intellectual disability. Input from a very experienced speech and language therapist was of great importance. Five groups with a total of 20 participants (15 different individuals) with mild to moderate intellectual disability and co‐morbid mental illness were run over a two‐year period. At the end of each group, an individualised "Staying Well Plan" was devised, to reduce the risk of future relapses. Findings – The group was very positively welcomed in the two pilot hospitals, by participants and members of the clinical teams. The key measure of the success of the programme is that the "Staying Well Plans" developed for the individuals are still in place two years after the completion of the first groups. Practical implications – The authors believe that this approach is of benefit to both the participants and their carers, stimulating positive engagement, open discussion about mental illness and reinforcing strategies for "Staying Well". Originality/value – This paper shows how a psychoeducational approach to severe mental illness in individuals with an intellectual disability is both possible and well received.